ELECTRICAL CONDUCTIVITY MODELS OF DIE CONFIGURATION FOR POLYPROPYLENE-REINFORCED MILLED CARBON FIBRE - Radzuan, N.A.M.; Sulong, A.B.; Somalu, M.R.; Suherman, H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Extrusion is one of the pre-mixing processes that produce a highly conductive polymer composite material when the appropriate die geometry is applied. However, the development of a conductivity model is still in the preliminary stage because the current model being used is unable to accurately predict the electrical conductivity. A generally effective media model and a modified fibre contact model were adapted in this study. To obtain a good agreement between the predicted model and the experimental data, the FCM model was modified by adapting the extrusion parameters, including the shear rate and rotational speed, into the equation. This was known as the MFCM with shear rate. This modified MFCM with shear rate showed a good correlation with the r-square of 0.99, as evidenced by the minimized gap between the predicted and experimental data. The MCF/PP composite produced using the rod die had the highest electrical conductivity of 3.7 S/cm as the fibre was aligned in the converging dies than in the sheet dies, which had an electrical conductivity of 1.3 S/cm.